The risk factors and pregnant women's willingness toward the SARS-CoV-2 vaccination in various countries: A systematic review and meta-analysis - Ricvan Dana Nindrea; Dovy Djanas; Warsiti; Ika Yulia Darma; Heni Hendriyani; Nissa Prima Sari (Elsevier, 2022)
Introduction: Pregnant women will benefit from research on immunization during pregnancy because they will have more accurate information on the SARS-CoV-2 vaccine. The purpose of this study was to determine the risk factors and pregnant women's desire to get the SARS-CoV-2 vaccine in various countries. Methods: A search of PubMed, ProQuest, and EBSCO for related publications published (January and December 2021) on risk factors and pregnant women's desire to get the SARS-CoV-2 vaccine in various countries. The Pooled Odds Ratio (POR) were calculated using fixed and random-effect analysis. The I-squared formula was used to calculate the heterogeneity. Egger's and Begg's tests were used to identify study bias. STATA 16.0 was used for data analysis. Results: This study revealed good practice has the highest POR (8.99), followed by received influenza vaccine last year (2.72), high perception of SARS-CoV-2 vaccine (2.70), >35 years (2.01), sufficient information about the SARS-COV-2 vaccine (1.94), higher school education (1.84), and third trimester (1.35) with pregnant women's desire toward the SARS-CoV-2 vaccination. The heterogeneity analysis revealed homogenous among risk factors in >35 years, high perception of SARS-CoV-2 vaccine, good practice, and third trimester (I2 ≤ 50%). In the articles combined in this study, there was no indication of study bias. Conclusion: The insights of this study might help the authorities in determining the most effective strategy to deploy SARS-CoV-2 mass immunization campaigns for pregnant women.